Peran Kualitas Layanan, Inovasi dan Kepercayaan dalam Meningkatkan Kepuasan Pengunjung Lapas Kelas IIB - Nurul Qomariah; Sarwito Sarwito; Abadi Sanosra; Mohammad Thamrin (BUDGETING : Journal of Business, Management and Accounting, 2023)
This study sought to ascertain the impact of service excellence, innovation, and trust on visitor happiness at Bondowoso, a class IIB facility. All of the residents are guests at Bondowoso Class II Prison. By using the judgment sampling technique, up to 120 respondents made up the sample size. The study hypothesis is tested using WarpPLS 7.0 structural equation model (SEM) analysis. To determine whether the used measuring instrument met the criteria for the measuring instrument test, validity and reliability tests were also performed. According to the findings, the service innovation variabel (X2) had a path coefficient value of 0.314 with a -value of 0.001 and the trust variabel (X3) had a path coefficient value of 0.454 with a -value of 0.001 for each variabel. The service quality variabel (X1) had a path coefficient value of 0.255 with a -value of 0.040. According to the study's findings, visitor satisfaction in Class II B Bondowoso Penitentiary is positively and significantly impacted by service quality, visitor trust, and service innovation.